First Language Attrition Of Lexical Structures In A Contact Situation With English: A Study Among Anaañ Bilingual Child - Etim, Victoria Enefiok; Okon, Bassey Andian; Okon, Margaret Mary (Advances in Social Sciences Research Journal, 2018)
This study examined first language (L1) Attrition of lexical items among bilingual children within Abak metropolis, Akwa Ibom State, Nigeria. First language (L1) attrition is the disintegration of the first language as a result of contact with second language (L2) or domination of the second language. The theories of language contact and language change and psycholinguistic question of accessibility is the theoretical framework for the study. An expo-facto design was used in the study and a purposive sampling was used to select 70 children from primary and secondary school of ages between 7 and 14 years who speak both English and Anaañ languages. Personality Background Questionnaire (PBQ), Ibadan Word list of 400 basic items and Picture Naming Task (PNT) were used to collect data for the study. This paper reveals that L1 attrition occurs as a result of non-constant usage of the L1 both at home and in school. Early exposure of the children to L2 also impedes their ability to fully develop the language of their mother tongue and consequently results in L1 attrition. The paper concludes that frequent use of L2, negative attitude to L1, motivation and age are the main reasons for lexical attrition in children. It is therefore recommended that the use of L1 by parents with their children at home be encouraged and L1 be included in the school curriculum for pupils and students at primary and secondary schools in order to prevent L1 attrition.